Groundwater Investigation by Combined Vertical Electrical Sounding and Magnetotelluric Sounding in Eastern Region of Mekong Delta, in the South of Vietnam - Nguyen Van, Giang; Nguyen Trong, Vu; Nguyen Huy, Vung (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
In the Eastern Region of Mekong Delta (South Vietnam) may contain brackish or saline water from land surface to great depth, both superficial Quaternary and deep Tertiary Alluvium. The combination of two geophysical methods, the Vertical Electrical Sounding (VES) for shallow investigation, and the Magnetotelluric Sounding (MTS) for deep investigation, provides a complete electrical image of the sedimentary series from the surface to the deep crystalline basement. It turns out very efficient to delineate the groundwater contamination in both superficial and deep aquifers. The combined results reveal a close correlation of the extent of the contamination with the paleogeomorphology of laterites, and subsequently with the paleorelief during the Tertiary and Quaternary times. Because this study area is very complicated hydrogeological structure, it is necessary to survey the current status of deep-water storage floors with geophysical measurement technologies to prevent groundwater pollution when exploiting groundwater here.